SAT0467 All 10-year cardiovascular risk scores are similar in patients with psoriatic arthritis and psoriasis. (15th June 2017) - Ikumi, N; Farkas, F; Szentpetery, A; Kirby, B; FitzGerald, O
Abstract : Background: Psoriatic arthritis (PsA) and Psoriasis (PsO) are associated with higher cardiovascular (CV) risk with higher risk in patients with a severe disease phenotype 1, 2 . Long-term CV risk is evaluated using several methods for the general population. Objectives: The aim of the study was to compare CV risk factors and 10-year CV risk scores between patients with PsA and those with PsO only. Methods: PsA patients fulfilling the CASPAR criteria and PsO with disease duration <10 years were enrolled consecutively from Rheumatology and Dermatology clinics. Fasting bloods were obtained for glucose, insulin and lipids. Patients underwent thorough physical examination, joint and skin assessments and completed questionnaires on health and quality of life. Four different CV risk scores were calculated: (1) Framingham Coronary risk score (FCS); (2) American College of Cardiology and American Heart Association (ACC/AHA) 10-year atherosclerotic cardiovascular disease (ASCVD) algorithm; (3) Systematic Coronary Risk Evaluation (SCORE) algorithm; and (4) QRISK2 (2016). Results: 232 patients (100 PsA and 132 PsO) were recruited with mean age 52.4 (±10.5) for PsA and 39.7 (±14.4) for PsO. Mean disease duration for PsA was 17.9 (±10) years. There were significantly more patients with hypertension (HTN) and metabolic syndrome in PsA group, and the patients taking DMARDs and/or biologics treatment were also higher compared to PsO. Fasting glucose, insulin, lipids, BMI and waist/hip ratio did not show significant differences. The mean FCS, ASCVD, SCORE and QRISK2 were significantly higher in PsA as compared to PsO (7.6±7.0% vs. 4.7±6.1%, P=0.0002; 8.4±8.2% vs. 4.5±5.8%, P<0.0001; 2.1±2.6% vs. 1.1±1.8%, P=0.0002; 11.2±9.9% vs. 5.2±6.4%, P<0.0001, respectively). However, after adjusting for age and sex, all CV risk scores were similar (P=0.21). Multiple regression analysis revealed that waist/hip ratio significantly correlated with all CV risk scores in both PsA and PsO. Conclusions: We found similar 10-year risk of CVD in PsA and PsO patients using FCS, ASCVD, SCORE and QRISK2. Waist/hip ratio had significant effect on all CV risk scores suggesting that central obesity should be managed appropriately to reduce long-term CVD in psoriatic disease. References: Eder L. Ther Adv Musculoskel Dis 2015. Ogdie A. ARD 2015. Disclosure of Interest: N. Ikumi: None declared, F. Farkas: None declared, A. Szentpetery: None declared, B. Kirby Grant/research support from: abbie, O. FitzGerald Grant/research support from: abbie, Pfizer, BMS, Consultant for: abbie, Pfizer, BMS, Celgene, Janssen, Novartis, UCB, Eli Lilly